A metal carbonyl–protein needle composite designed for intracellular CO delivery to modulate NF-κB activity1. Issue 11 (13th November 2015) - Inaba, Hiroshi; Sanghamitra, Nusrat J. M.; Fujita, Kenta; Sho, Takeya; Kuchimaru, Takahiro; Kitagawa, Susumu; Kizaka-Kondoh, Shinae; Ueno, Takafumi
<x xml:space="preserve">Abstract</x> An efficient intracellular carbon monoxide delivery system using a cell-penetrating protein needle was developed for modulation of NF-κB activity.